2007
DOI: 10.1088/0022-3727/40/24/010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of strained GaAs1−ySby (0.16 ≤ y ≤ 0.69) quantum wells on InP substrates

Abstract: Pseudomorphic GaAs 1−y Sb y quantum wells with 0.16 y 0.69 on (0 0 1) InP substrates have been grown using metal-organic chemical vapour deposition. High resolution x-ray diffraction and transmission electron microscopy analysis are used to quantify the layer thicknesses and compositions. Studies of the optical properties suggest that a transition from type-I to type-II band alignment occurs at an antimony concentration of approximately y = 0.30. The interband optical transition energies simulated using a ten-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One-dimensional metal/semiconductor heterojunction nanomaterials are of key importance because of their novel structures, unique electrical and optical properties and central roles in fabricating electronic nanodevices [1,2]. In nanodevices, heterojunction nanomaterials can effectively control electron, positive hole and exciton transmission and thus possess a unique Coulomb blockade effect [3], Schottky diode behaviour [4], Ohmic contact property [5] and photoluminescence property [6], using which singleelectron transistors, electronic and optoelectronic devices, photodetection devices, biological/chemical sensors, logic 1 Author to whom any correspondence should be addressed. circuits, etc have been successfully manufactured.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional metal/semiconductor heterojunction nanomaterials are of key importance because of their novel structures, unique electrical and optical properties and central roles in fabricating electronic nanodevices [1,2]. In nanodevices, heterojunction nanomaterials can effectively control electron, positive hole and exciton transmission and thus possess a unique Coulomb blockade effect [3], Schottky diode behaviour [4], Ohmic contact property [5] and photoluminescence property [6], using which singleelectron transistors, electronic and optoelectronic devices, photodetection devices, biological/chemical sensors, logic 1 Author to whom any correspondence should be addressed. circuits, etc have been successfully manufactured.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of the GaAs 1Ày Sb y alloy system by the introduction of N has been studied by several groups for growth on GaAs [38,39], GaSb [40] and InP [7,41,42] substrates. The addition of N leads to a substantial band-bowing in the GaSb 1Àz N z [43], and it is seen as an alternative material for InGaAsN.…”
Section: Growth Chemistry and Gaas 1ày Sb Y Compositionmentioning
confidence: 99%
“…Recent studies on finite-time thermodynamic engines and heat pumps have shown that their stability and their thermodynamic performance are often governed by the same parameters. It has been observed that the system stability usually weakens as its thermodynamic properties improve [5][6][7][8][9][10][11][12][13][14][15][16][17]. Consequently, these parameters need to be tuned to achieve an optimal trade-off between favorable thermodynamic and dynamic properties.…”
Section: Introductionmentioning
confidence: 99%